Pancreatic stone protein (PSP) and pancreatitis-associated protein (PAP): a protocol of a cohort study on the diagnostic efficacy and prognostic value of PSP and PAP as postoperative markers of septic complications in patients undergoing abdominal surgery (PSP study). Issue 3 (6th March 2014) - Fisher, Oliver Maximilian; Oberkofler, Christian Eugen; Raptis, Dimitri Aristotle; Soll, Christopher; Béchir, Markus; Schiesser, Marc; Graf, Rolf
Abstract : Introduction: Major abdominal surgery leads to a postoperative systemic inflammatory response, making it difficult to discriminate patients with systemic inflammatory response syndrome from those with a beginning postoperative infectious complication. At present, physicians have to rely on their clinical experience to differentiate between the two. Pancreatic stone protein (PSP) and pancreatitis-associated protein (PAP), both secretory proteins produced by the pancreas, are dramatically increased during pancreatic disease and have been shown to act as acute-phase proteins. Increased levels of PSP have been detected in polytrauma patients developing sepsis and PSP has shown a high diagnostic accuracy in discriminating the severity of peritonitis and in predicting death in intensive care unit patients. However, the prognostic value of PSP/PAP for infectious complications among patients undergoing major abdominal surgery is unknown. Methods and analysis: 160 patients undergoing major abdominal surgery will be recruited preoperatively. On the day before surgery, baseline blood values are attained. Following surgery, daily blood samples for measuring regular inflammatory markers (c-reactive protein, procalcitonin, interleukin-6, tumour necrosis factor-α and leucocyte counts) and PSP/PAP will be acquired. PSP/PAP will be measured using a validated ELISA developed in our research laboratory. Patient's discharge marks the end of his/her trial participation. Complication grade including mortality and occurrence of infectious postoperative complications according to validated diagnostic criteria will be correlated with PSP/PAP values. Total intensive care unit days and total length of stay will be recorded as further outcome parameters. Ethics and dissemination: The PSP trial is a prospective monocentric cohort study evaluating the prognostic value of PSP and PAP for postoperative infectious complications. In addition, a comparison with established inflammatory markers in patients undergoing major abdominal surgery will be performed to help evaluate the role of these proteins in predicting and diagnosing infectious and other postoperative complications. Institution ethics board approval ID: KEKZH-Nr. STV 11-2009. Trial registration: ClinicalTrials.gov: NCT01258179 .